Assessing the impact of covid-19 on the delivery and reception of ESP education for engineering students in Croatia - Ivanka Ferčec; Yvonne Liermann-Zeljak (Scripta Manent)
The COVID-19 pandemic has irreversibly changed education at all levels and greatly impacted its delivery, as in response to the crisis, both instructors and students had to switch abruptly from traditional face-to-face to virtual classes, i.e. emergency remote teaching (ERT), which was entirely new, demanding, and challenging for both parties. The aim of the paper is to explore engineering students’ and ESP instructors’ experience and the main challenges both stakeholders faced in the initial period of ERT. For that purpose, the data were collected using two (anonymous) questionnaires created by using Google Forms and delivered in summer 2020 to the students by sharing the link on Loomen, and in autumn 2020 to the ESP instructors by sending the link via email. The results indicate that the main challenges of 128 engineering students from Osijek, Croatia, who took part in the survey, mainly referred to lack of motivation and poor time management and organisation, while the main challenges indicated by 52 ESP instructors from Croatia who took part in the survey were lack of in-person interaction and time and effort invested in preparing for classes. The student-related research results show that teaching quality and effectiveness can be improved by motivating and supporting our students, and adapting more readily to online classes in the event of new or continued lockdown. The instructor- related research results reveal that the majority of Croatian ESP instructors (i.e. 85%) did not have any experience with online classes prior to the pandemic and only about one fourth of them (i.e. 27%) confirmed that they received some training in technology-related teaching skills, which points to the importance and need for continuing education and professional development for instructors.